FAKTOR YANG MEMPENGARUHI KEPUASAAN KONSUMEN DALAM MEMILIH KULINER TRADISIONAL KOTA BOGOR - Dyah Prabandari; Kania Sofiantina Rahayu; Annisa Rizkiriani; Melewanto Patabang; Natasha Indah Rahmani (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2023)
The condition of culinary tourism in Bogor is dominated by modern cuisine, which has led to the exclusion of traditional cuisine. This research aims to determine the factors influencing tourist or consumer satisfaction in choosing traditional culinary delights in Bogor City. The method used in this study is quantitative. The analysis used in this research to determine the level of feasibility of the questionnaire used was the validity and reliability test to test the questionnaire for determining the attributes of tourist or consumer satisfaction. The subsequent analysis used in this research is a regression analysis to determine the factors influencing consumer satisfaction in choosing traditional culinary delights in Bogor City. The research results show that culinary products can make tourists or consumers satisfied. Bogor City's traditional culinary products consist of a variety of products with varying levels of taste, quality, presentation, and packaging. The price, service, or motivation don't affect tourist satisfaction when choosing culinary.